Foreign Language Performance and Learners: Intuitions about Verbal Interaction - Cots, Josep M. (Miscelánea: A Journal of English and American Studies, 1994)
The aim of this paper is to analyze the relationship existing between the oral performance of a subject in a "gatekeeping" encounter such as an office appointment with a teacher and his/her definition of the situation and of the role that language plays in it. In a real context of language use, the outcome is connected with the speakers' fulfillment of the goal with which they approached the encounter, a fulfillment which does not exclusively depend on the nature of the object being negotiated but also on how it is negotiated.